Gold nanorod-mediated near-infrared laser ablation: in vivo experiments on mice and theoretical analysis at different settings. (17th February 2017) - Mooney, Rachael; Schena, Emiliano; Saccomandi, Paola; Zhumkhawala, Ali; Aboody, Karen; Berlin, Jacob M.
Abstract: Purpose: The aim of the present study was the in vivo assessment of the effects of gold nanorod (AuNR)-mediated laser ablation (LA) of flank xenograft tumours. We investigated: the differences between intra-tumoural ( T IT ) and surface tumoural temperature ( T S ); the influence of AuNRs concentration and laser power (P) on both these temperatures and on tumour regression. Lastly, experimental data were used to validate a theoretical model developed to predict the effects of AuNR-mediated LA. Materials and methods: Thirty-two nude mice were treated using near-infra-red light at two P, 3 d after injecting increasing AuNR doses. T IT and T S were recorded during the procedure by two thermocouples, one located within the tumour and the other one on the skin adjacent to the tumour. Tumour regression was assessed 2 d after near-infra-red exposure via Xenogen imaging. A three-dimensional temperature map was obtained by finite element modelling. Results: T IT and T S difference is substantial when AuNRs are injected. Moreover, the maximum temperature reached is strongly influenced by both P and AuNR concentration. Tumours heated above 55 °C experienced regression. Good agreement between experimental and theoretical T IT was found (maximum difference of 4 °C). Conclusions: Data show significant influence of P and AuNR concentration on the temperatures reached during AuNR-mediated LA of solid tumours. T S and T IT difference increases with AuNRs concentration. Simulated temperatures agree quite well with experimental data. Together, these results represent the first step towards a rationally designed strategy to select the most promising laser settings and AuNRs concentration to improve solid tumour treatment outcomes.